2017
DOI: 10.1590/1678-457x.26716
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid and phenolic contents, antioxidant capacity and flavonoids composition of Brazilian Savannah native fruits

Abstract: The Brazilian Savannah, known as Cerrado, produces several native fruits, which have been investigated as potential sources of antioxidant substances (Souza et al., 2012). Cagaita (Eugenia dysenterica DC), cerrado cashew (Anacardium othonianum Rizz.) and gabiroba (Campomanesia adamantium (Cambess.) O. Berg) are used as food, as well as nutraceuticals in folk medicine, with the potential of contributing to the economy of the Cerrado. These fruits exhibit high moisture contents (Cardoso et al., 2011; Pereira et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 30 publications
2
23
2
5
Order By: Relevance
“…Seven compounds identified in this work were also previously observed by de Brito et al 18 Moreover, Gordon et al 36 detected four compounds in A. occidentale pseudofruits that were also identified in this work: myrecetin-3-O-rhamnoside, quercetin 3-O-galactoside, quercetin 3-O-glucoside and kaempferol 3-O-glucoside. Two compounds detected in this work were previously observed by Alves et al 37 in A. othonianum, who used liquid chromatography with an automatic display, quaternary pump, and diode array detector (HPLC-ESI-MS/MS) and detected two flavonoids (myricetin rutinoside and myricetin derivative) and five anthocyanins (cyanidin hexoside, cyanidin 3-glucoside, delphinidin rutinoside, pelargonidin hexoside and peonidin 3-glucoside). Chlorogenic acid (5-O-caffeoylquinic acid), a phenolic compound, was the only compound from the hydroxycinnamic acid family found in the A. othonianum accessions.…”
Section: Characterization Of Phenolic and Flavonoid Compoundssupporting
confidence: 74%
See 1 more Smart Citation
“…Seven compounds identified in this work were also previously observed by de Brito et al 18 Moreover, Gordon et al 36 detected four compounds in A. occidentale pseudofruits that were also identified in this work: myrecetin-3-O-rhamnoside, quercetin 3-O-galactoside, quercetin 3-O-glucoside and kaempferol 3-O-glucoside. Two compounds detected in this work were previously observed by Alves et al 37 in A. othonianum, who used liquid chromatography with an automatic display, quaternary pump, and diode array detector (HPLC-ESI-MS/MS) and detected two flavonoids (myricetin rutinoside and myricetin derivative) and five anthocyanins (cyanidin hexoside, cyanidin 3-glucoside, delphinidin rutinoside, pelargonidin hexoside and peonidin 3-glucoside). Chlorogenic acid (5-O-caffeoylquinic acid), a phenolic compound, was the only compound from the hydroxycinnamic acid family found in the A. othonianum accessions.…”
Section: Characterization Of Phenolic and Flavonoid Compoundssupporting
confidence: 74%
“…detected four compounds in A. occidentale pseudofruits that were also identified in this work: myrecetin‐3‐ O ‐rhamnoside, quercetin 3‐ O ‐galactoside, quercetin 3‐ O ‐glucoside and kaempferol 3‐ O ‐glucoside. Two compounds detected in this work were previously observed by Alves et al . in A. othonianum , who used liquid chromatography with an automatic display, quaternary pump, and diode array detector (HPLC‐ESI‐MS/MS) and detected two flavonoids (myricetin rutinoside and myricetin derivative) and five anthocyanins (cyanidin hexoside, cyanidin 3‐glucoside, delphinidin rutinoside, pelargonidin hexoside and peonidin 3‐glucoside).…”
Section: Resultsmentioning
confidence: 99%
“…31 A strong correlation between the content of phenolic compounds and the antioxidant capacity, through the DPPH and FRAP assays, has also been reported in studies with Brazilian fruits, including caju-do-cerrado, gabiroba, cagaita and camu-camu fruits. 31,50 The results obtained by these authors suggest that ascorbic acid and phenolic compounds may be the most important contributors to the antioxidant capacity presented by the B. tomentosa fruit extract studied in this study.…”
Section: Antioxidant Capacity Determinationmentioning
confidence: 62%
“…Alves et al evaluated the antioxidant capacity of the cashew, gabiroba, and cagaita fruits, by different methods, including the DPPH and FRAP assays, and found a significant correlation between the antioxidant capacity and the ascorbic acid content. 50 In another study, using the FRAP method to evaluated the antioxidant capacity of Brazilian tropical fruits, the authors reported a positive correlation between ascorbic acid content and antioxidant capacity. 31 A strong correlation between the content of phenolic compounds and the antioxidant capacity, through the DPPH and FRAP assays, has also been reported in studies with Brazilian fruits, including caju-do-cerrado, gabiroba, cagaita and camu-camu fruits.…”
Section: Antioxidant Capacity Determinationmentioning
confidence: 96%
“…Concerning the result of the antioxidant capacity by DPPH (Table 2), the grumixama cultivated in Goiás has the highest radical scavenging capacity among the grumixama cultivated in São Paulo (MACHADO et al, 2017), the fruits native to the Cerrado (ALVES et al, 2017) and Alaskan wild blueberry (GRACE et al, 2014). The grumixama seed has high antioxidant capacity (TEIXEIRA et al, 2015), which could partially explain the significant difference between data of the fruit from São Paulo (pulp) (MACHADO et al, 2017) and Goiás (whole fruit).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%